Expression of HER2/neu in gastric adenocarcinoma and its correlation with serum HER2/neu level and E-cadherin expression - Ishan Pandey; Vatsala Misra; Aprajita T Pandey; Amita Verma (Wolters Kluwer Medknow Publications, 2022)
Aim: To assess HER2/neu expressions and correlate with E-cadherin and Serum HER2 level in gastric carcinoma. Method: 31 gastric biopsies and 1 resected specimen were taken in the study with patient details and stained with H and E for histopathological details following Lauren's classification. Immunohistochemistry for HER2 and E-cadherin expression was conducted followed by serum HER2/neu ELISA. Result: Adenocarcinoma with 61% diffuse, 29% intestinal, and 10% other type were observed with predominant HER2 immunoexpression in intestinal-type than in diffuse-type adenocarcinoma. Other observations marked 44% as 3+/positive and 56% as 2+/equivocal in intestinal type while 26% cases as 3+/positive, 69% as 2+/equivocal, and 1% as 1+/negative were observed in diffuse type. The data presented 33% membranous positivity and 67% both membranous + cytoplasmic positivity in intestinal type while 2% showed membranous positivity, 47% both membranous + cytoplasmic, and 42% only cytoplasmic positivity in diffused type. On comparing the localization pattern of HER2 and E-cadherin, 25% of cases showed membranous staining while 50% of cases showed membranous with cytoplasmic staining for both. No cytoplasmic HER2 staining as well as no any staining for E-cadherin was shown by 6% cases. Conclusion: Thus, it can be concluded that cytoplasmic expression of HER2 in gastric adenocarcinoma (mainly diffuse type) may be due to shedding of its extracellular domain, leading to loss of membranous E-cadherin expression on immunohistochemistry. The loss of membranous expression of E-cadherin and increased serum HER2 ELISA were correlated well with these findings.